Non-equilibrium dynamics contribute to ion selectivity in the KcsA channel. - Van Ngo; Darko Stefanovski; Stephan Haas; Robert A Farley (PLoS ONE, 2014)
The ability of biological ion channels to conduct selected ions across cell membranes is critical for the survival of both animal and bacterial cells. Numerous investigations of ion selectivity have been conducted over more than 50 years, yet the mechanisms whereby the channels select certain ions and reject others are not well understood. Here we report a new application of Jarzynski's Equality to investigate the mechanism of ion selectivity using non-equilibrium molecular dynamics simulations of Na(+) and K(+) ions moving through the KcsA channel. The simulations show that the selectivity filter of KcsA adapts and responds to the presence of the ions with structural rearrangements that are different for Na(+) and K(+). These structural rearrangements facilitate entry of K(+) ions into the selectivity filter and permeation through the channel, and rejection of Na(+) ions. A mechanistic model of ion selectivity by this channel based on the results of the simulations relates the structural rearrangement of the selectivity filter to the differential dehydration of ions and multiple-ion occupancy and describes a mechanism to efficiently select and conduct K(+). Estimates of the K(+)/Na(+) selectivity ratio and steady state ion conductance for KcsA from the simulations are in good quantitative agreement with experimental measurements. This model also accurately describes experimental observations of channel block by cytoplasmic Na(+) ions, the "punch through" relief of channel block by cytoplasmic positive voltages, and is consistent with the knock-on mechanism of ion permeation.